Symptom and indications for surgery in patients with lumbar discopathy - Skandaroghli, Behzad; Amani, Firouz; Altafi, Davar; Majid, Azari (International Surgery Journal, 2016)
Background: Outdated Lumbar discopathy is a deterioration of the intervertebral disc of the lumbar spine level. Spondylosis is a process that affects the entire axial skeleton and includes a stage of degenerative changes which occur at the cellular and biochemical level. Due to high occurrence rate of back discs over the society and its importance. The aim of this study was determine symptom and indications for surgery in patients with lumbar discopathy. Methods: This is a descriptive-analytical study that has been done on 90 patient’s candidate for lumbar discopathy surgery between 2009 and 2012. Their general condition and level of satisfaction after surgery were evaluated by phone calls of the patients Results: From all 90 patients, 55 (66.1%) were men and 35 (39.9%) were women with sex ratio l to 1.6. From all patients, 41 (45.6%) were self- employed and worker and most of them with 46.7% were hospitalized for 4 days. Indications of neurologic deficit - Limits daily activations - Intractable pain medication altogether with 42.3% were the most. 84 (93.3%) patients were recovered respect to before surgery. 9 patients (10%) had recurrence of symptoms. Indications of intractable pain medication with 36 (40%) patients had a considerable amount. L4- L5 involvement level with 44 cases (48.9%) respect to other levels has been the most. Conclusions: Based on the results, the most indications which patients had for surgery was intractable pain medication which in most of them patients were recovered and highly satisfied. According to the results, patients who have intractable pain and other patients with different indications could benefit from a surgical treatment.